2019
DOI: 10.4103/jpbs.jpbs_80_19
|View full text |Cite
|
Sign up to set email alerts
|

Isthmus incidence in human permanent mandibular first molars of a South Indian population: A cone-beam computerized tomographic study

Abstract: Aim: This study aimed to analyze incidence of isthmus in human permanent mandibular first molar teeth using cone-beam computed tomographic imaging techniques in a South Indian population. Materials and Methods: Three hundred permanent mandibular first molar teeth were collected, cleaned, and stored in normal saline. They were divided into groups (GPs) I and II based on number of roots, and were further subdivided (right and left [RL] subgroups A and B for GP I; and RL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
5
1
2
Order By: Relevance
“…2013, Karunakaran et al . 2019). As the frequency of this isthmus diminishes towards the apical third (Karunakaran et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013, Karunakaran et al . 2019). As the frequency of this isthmus diminishes towards the apical third (Karunakaran et al .…”
Section: Discussionmentioning
confidence: 99%
“…Mesial roots of human mandibular molars were selected because they have a high incidence of isthmus, ranging from 54%-100% (de Pablo et al 2010, Harris et al 2013, Karunakaran et al 2019. As the frequency of this isthmus diminishes towards the apical third (Karunakaran et al 2019), the present study included roots with an isthmus connecting the whole length of the two main canals (type 1), as well as roots with isthmuses only in the cervical and middle thirds (type 2). The data obtained from the isthmus of the apical third are therefore half that from the other thirds, 7 versus 14 per group ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In mandibular molars, an isthmus is frequently observed in sections between 3 and 4 mm from the apex ( Figure 15 ). Karunakaran et al [ 45 ] reported that the prevalence of isthmuses in the mesial roots of mandibular first molars was 97.2%, while the prevalence in distal roots was 39%. Furthermore, von Arx [ 46 ] analyzed the occurrence of a canal isthmus in mandibular molars during endodontic surgery.…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…O objetivo do tratamento endodôntico é tratar ou prevenir a periodontite apical, promovendo a antissepsia e limpeza do sistema de canais radiculares para uma posterior obturação tridimensional; entretanto, anatomias complexas, como istmos, são uma das principais variações anatômicas que podem dificultar a busca por este objetivo (Hsu;Kim, 1997;Ricucci;Siqueira, 2010;Pecora et al, 2013;Estrela et al, 2015b;Kim et al, 2016;Karunakaran et al, 2019). Com isso, estudos anatômicos que buscam identificar e descrever a incidência desta variação nas diferentes populações são de extrema relevância para o endodontista.…”
Section: Discussionunclassified
“…Segundo Estrela et al (2015b), o dente que apresenta a maior incidência de istmos é o primeiro molar inferior; este normalmente apresenta duas raízes, sendo que na raiz mesial ocorre um forte achatamento proximal, apresentando na maioria dos casos 2 canais (de Pablo et al, 2010), com uma forte prevalência de istmos entre estes (Teixeira et al, 2003;Mannocci et al, 2005;Gu et al, 2009;de Pablo et al, 2010;Fan et al, 2010;Pecora et al, 2013;Lima et al, 2014;Mehrvarzfar et al, 2014;Estrela et al, 2015b;Tahmasbi et al, 2017;Srivastava et al, 2018;Karunakaran et al, 2019;Chuppani Dastgerdi et al, 2020); justificando assim a escolha da raiz mesial de primeiros molares inferiores como objeto deste estudo.…”
Section: Discussionunclassified